COMMUNITY EMPOWERMENT AS AN EFFORT TO PREVENT CHILD MARRIAGE - Masruroh Masruroh; Bernadeta Verawati (Journal of Midwifery, 2019)
Background: Indonesia is one of the ten countries in the world with the highest absolute number of child marriage. It is estimated that one in five girls in Indonesia gets married under 18 years old. Lack of knowledge about reproductive health and strong religious beliefs about marriage law are the reasons for child marriage.Objective: to formulate a model of community empowerment as an effort to prevent child marriageMethod: This study used qualitative research with descriptive approach. The study was conducted in August-September 2019 in seven Junior High Schools in Semin Sub-District, Gunungkidul. There were seven homeroom teachers as the main informants, seven principals of Junior High School as the key informants, and seven students' parents as the supporting informants. The informants were selected by using purposive sampling. The data were collected through in-depth interviews and Focus Group Discussion. The data were analyzed using the interactive model of Miles and Huberman.Results: the formulation of the model consisted of the input, processing and output stages. Input Stage: (1) family and community (2) related institutions (3) schools (4) teachers. Processing Stage: (1) school activities, (2) the role of the homeroom teachers, (3) tigo matur setunggal mabrur task force. Output stage: (1) good attitude, (2) independence, (3) decision making. Outcome Stage: preventing child marriage.